The Impact Of Microfinance On Households’ Socioeconomic Performance: A Proposed Mediation Model - W Muhammad Zainuddin B Wan Abdullah; Sarina Binti Ismail; Mohd Hassan Che Haat; Hafiz Muhammad Zia-Ul-Haq; Wan Nur Rahini Aznie Zainudin (Korea Distribution Science Association, 2024)
Indexed by WOS/ Scopus